Sleeping Eurasian oystercatchers adjust their vigilance in response to the behaviour of neighbours, human disturbance and environmental conditions. (25th June 2020) - McBlain, M.; Jones, K. A.; Shannon, G.
Abstract: Vigilance is a costly behaviour but it enables animals to detect and avoid threats of predation and intraspecific competition. To compensate for the increased risk while sleeping, many bird species have evolved eye‐blinking strategies called peeking, which allows vigilance to persist in a sleep‐like state. However, the drivers of vigilance behaviour during sleep have rarely been explored. We investigated how social factors, anthropogenic disturbance and environmental conditions affected the sleep‐vigilance trade‐off in the Eurasian oystercatcher ( Haematopus ostralegus ). Data were collected on the frequency, total duration and average duration of peeking at two locations on the Menai Strait, North Wales. Our results reveal that exposure to anthropogenic disturbance, particularly the presence of people exercising dogs, led to an increase in vigilance duration and reduced time sleeping, while increasing boat traffic resulted in elevated levels of peek frequency, but the overall duration of vigilance was in fact reduced. Furthermore, oystercatchers adjust their vigilance behaviour according to social context, with reduced levels of individual vigilance when a greater number of animals were present. However, if surrounding neighbours were awake – then the observed animal was more likely to be alert, demonstrating the importance of monitoring the behaviour of conspecifics. Likewise, the temperature and wind speed influenced vigilance with elevated levels of peek frequency observed in warmer and windier conditions. Oystercatchers are able to make fine‐scale adjustments to their vigilance behaviour while asleep, which reduces the risk of external threats such as predators. Nevertheless, they are making these decisions against the backdrop of a finely balanced energy budget, particularly during the winter months. Increased levels of human activity and disturbance may elevate the costs of vigilance and ultimately have fitness implications for this species. Abstract : We investigated how social factors, anthropogenic disturbance and environmental conditions affected the sleep–vigilance trade‐off in the Eurasian oystercatcher. Our results reveal that exposure to anthropogenic disturbance led to an increase in vigilance behaviour and reduced time sleeping, which may have fitness implications, particularly when resources are scarce and energy demand is high. Furthermore, oystercatchers are able to make fine‐scale adjustments to their vigilance behaviour according to social context (number and behaviour of neighbouring birds) and environmental conditions (temperature and wind speed).